Nanomedicine for Cancer Therapy From Chemotherapeutic to Hyperthermia-Based Therapy - Kumar, Piyush; Srivastava, Rohit (Nanotheranostics, 2017)
This Brief focuses on the cancer therapy available till date, from conventional drug delivery to nanomedicine in clinical trial. In addition, it reports on future generation based nanotherapeutics and cancer theranostic agent for effective therapeutic diagnosis and treatment. Breast cancer was chosen as the model system in this review. The authors give emphasis to multiple drug resistance (MDR) and its mechanism and how to overcome it using the nanoparticle approach. .